Pengaruh Penggunaan Fintech Dan Lifesytle Terhadap Kemampuan Pengelolaan Keuangan Di Bengkulu - Afriansyah, Berlian; Meriana, Meriana; Nurjanah, Amalia (Politeknik Raflesia Press, 2024)
This research is to determine the influence of the use of Fintech and lifestyle on the financial management abilities of students in city districts in Bengkulu province. The research method used in this research is a quantitative method which uses a questionnaire as a research instrument and is measured using a Likert scale. The results of this research show that Fintech has an influence on Financial Management Ability. This shows that the better the Fintech, the better the Financial Management Capabilities will be. while Lifestyle also influences Financial Management Ability. This research shows that the higher the style, the higher the financial management ability